Peran Konselor Dalam Mengatasi Bullying di Lingkungan Sekolah SMP Terpadu Daar Al Hikmah Seputih Mataram - Silsi Ivana Pratiwi (CV. Lentera Literasi Indonesia, 2026)
The purpose of this study is to describe the role of counselors in addressing bullying in junior high school environments, identify the types of bullying in school environments, and identify the factors that cause bullying. The method used in this study is qualitative descriptive. Data collection techniques included interviews, observation, and documentation with the student affairs officer at Daar Al Hikmah Seputih Mataram Integrated Junior High School. Data analysis used the Miles and Huberman analysis model. After data analysis, the results showed that the student affairs officer plays an important role as a counselor who can address bullying behavior in the school environment. The student affairs officer, who serves as an informant, motivator, facilitator, mediator, and evaluator, can take steps to prevent bullying in the school environment and can effectively identify the types and factors that cause bullying at SMP Terpadu Daar Al Hikmah Seputih Mataram.